Nontargeted metabolomics reveals the potential mechanism underlying the association between birthweight and metabolic disturbances - Xiao Zhai; Jieying Liu; Miao Yu; Qian Zhang; Ming Li; Nan Zhao; Juntao Liu; Yingna Song; Liangkun Ma; Rongrong Li; Zongxu Qiao; Guifen Zhao; et al. (BMC, 2023)
Abstract Aims The aim of this study was to characterize the metabolites associated with small- and large-gestational-age newborns in maternal and cord blood, and to investigate potential mechanisms underlying the association between birthweight and metabolic disturbances. Research design and methods We recorded detailed anthropometric data of mother-offspring dyads. Untargeted metabolomic assays were performed on 67 pairs of cord blood and maternal fasting plasma samples including 16 pairs of small-for-gestational (SGA, < 10th percentile) dyads, 28 pairs of appropriate-for-gestational (AGA, approximate 50 percentile) dyads, and 23 pairs of large-for-gestational (LGA, > 90th percentile) dyads. The association of metabolites with newborn birthweight was conducted to screen for metabolites with U-shaped and line-shaped distributions. The association of metabolites with maternal and fetal phenotypes was also performed. Results We found 2 types of metabolites that changed in different patterns according to newborn birthweight. One type of metabolite exhibited a "U-shaped" trend of abundance fluctuation in the SGA-AGA-LGA groups. The results demonstrated that cuminaldehyde level was lower in the SGA and LGA groups, and its abundance in cord blood was negatively correlated with maternal BMI (r = -0.352 p = 0.009) and weight gain (r = -0.267 p = 0.043). 2-Methoxy-estradiol-17b 3-glucuronide, which showed enrichment in the SGA and LGA groups, was positively correlated with homocysteine (r = 0.44, p < 0.001) and free fatty acid (r = 0.42, p < 0.001) in maternal blood. Serotonin and 13(S)-HODE were the second type of metabolites, denoted as "line-shaped", which both showed increasing trends in the SGA-AGA-LGA groups in both maternal and cord blood and were both significantly positively correlated with maternal BMI before pregnancy. Moreover, cuminaldehyde, serotonin, 13(S)-HODE and some lipid metabolites showed a strong correlation between maternal and cord blood. Conclusions These investigations demonstrate broad-scale metabolomic differences associated with newborn birthweight in both pregnant women and their newborns. The U-shaped metabolites associated with both the SGA and LGA groups might explain the U-shaped association between birthweight and metabolic dysregulation. The line-shaped metabolites might participate in intrauterine growth regulation. These observations might help to provide new insights into the insulin resistance and the risk of metabolic disturbance of SGA and LGA babies in adulthood and might identify potential new markers for adverse newborn outcomes in pregnant women.